Single-cell dissection of PTM-related networks reveals an immunosuppressed osteosarcoma ecosystem - Chen, Jingyu; Zhang, Wei; Yan, Hai; Chen, Jinyu; Liu, Hanrui; Zhou, Xingyu; Zhang, Haiping; Cheng, Dongdong (Frontiers in Molecular Biosciences, 2025)
BackgroundOsteosarcoma remains lethal for many patients with metastatic or relapsed disease. Post-translational modifications (PTMs) regulate protein signaling and may shape the tumor microenvironment and clinical behavior in osteosarcoma, but PTM-anchored transcriptomic programs are as yet not well defined.MethodsWe integrated single-cell RNA sequencing from GSE162454 with curated PTM and immune gene sets to build a PTM-related framework for osteosarcoma. Tumor cell differentially expressed genes were intersected with PTM and immune repertoires to derive candidates. A PTM-related prognostic score was trained in TARGET-OS and validated in GSE21257 and GSE16091. Immune infiltration and microenvironment features were profiled using ssGSEA, Estimation of STromal and Immune cells in MAlignant Tumor tissues using Expression (ESTIMATE) data, and Tumor Immune Dysfunction and Exclusion (TIDE) scores. Model interpretation used SHapley Additive exPlanations (SHAP) and single-cell localization. GRN was prioritized for exploration of immune correlations and in vitro loss-of-function assays in U2OS and HOS cells.ResultsThe three-way intersection yielded 298 genes. The PTM-related score stratified overall survival in training and validation cohorts and remained independent of clinical covariates. High scores aligned with an immunosuppressed, stroma-rich microenvironment, with lower ImmuneScores and ESTIMATE scores, enrichment of myeloid and regulatory lineages, higher dysfunction and exclusion by TIDE, and reduced cytolytic, interferon, and antigen-presentation programs. SHAP highlighted a compact driver set enriched in malignant and stromal compartments. GRN showed strong contribution and consistent single-cell localization. Elevated GRN correlated with plasmacytoid dendritic cells, myeloid-derived suppressor cells (MDSCs), macrophages, regulatory T cells (Tregs), and multiple inhibitory checkpoints and with diminished immune effector functions. GRN silencing reduced proliferation, clonogenicity, migration, and invasion in osteosarcoma cells.ConclusionA PTM-anchored transcriptomic signature captures prognostic heterogeneity in osteosarcoma and links adverse outcome to an immunosuppressed microenvironment. GRN emerges as a tumor- and stroma-intrinsic mediator of immune suppression and malignant traits and represents a biologically grounded target for future mechanistic and therapeutic studies.